Intestinal loads of OXA-48-producing Klebsiella pneumoniae in colonized patients determined from surveillance rectal swabs. (August 2021) - Lázaro-Perona, Fernando; Rodríguez-Tejedor, María; Ruiz-Carrascoso, Guillermo; Díaz-Pollán, Beatriz; Loeches, Belén; Ramos-Ramos, Juan Carlos; Mingorance, Jesús
Abstract: Objectives: To determine quantitatively the extent of intestinal colonization by OXA-48-producing Klebsiella pneumoniae (KpOXA) in hospitalized patients. Methods: The load of the OXA-48 β-lactamase gene in rectal swabs from 147 colonized patients was measured by quantitative PCR. The load was calculated relative to the total bacterial population (represented by the 16S rRNA gene) using the ΔΔCt method and pure cultures of OXA-48-producing K. pneumoniae as reference samples. The relative loads of the epidemic K. pneumoniae clones ST11 and ST405 were also measured. Results: The relative intestinal loads of the OXA-48 β-lactamase gene, RLOXA-48, in hospitalized patients were high. The median RLOXA-48 was -0.42 (95% confidence interval (CI): -0.60 to -0.16), close to that of a pure culture of OXA-48-producing K. pneumoniae (RLOXA-48 = 0). In those patients colonized by the KpOXA clones ST11 (51/147, 34.7%) and ST405 (14/147, 9.5%), the relative loads of these clones were similarly high (median RLST11 = -1.1, 95% CI: -1.64 to -0.92; median RLST405 = -1.3, 95% CI: -1.76 to -0.96). Patients that had received previous antibiotic treatments and those that developed infections by KpOXA had significantly higher RLOXA-48 values: -0.32 (95% CI: -0.58 to -0.20) vs -1.07 (95% CI: -2.43 to -0.35) and -0.26 (-0.77 to -0.23) vs -0.47 (-0.74 to -0.28), respectively. Conclusions: Colonization by KpOXA in hospital patients involves intestinal loads much higher than the K. pneumoniae loads reported in the normal microbiota, reaching levels close to those of pure KpOXA cultures in many cases and largely replacing the host microbiota. Graphical abstract: Image 1